Communication strategies for managing material flows in construction: the relationship between marketing, logistics and consumer trust (Economics and region, 2025)
The article summarizes the theoretical and methodological principles of forming communication strategies for managing material flows in construction. The reasons for ineffective communication are considered (lack of standardized procedures and training, insufficient representation of project stakeholders). It is shown that ensuring transparency of material flows and accelerating response time to needs is critical for modern logistics models. The features of material flows in construction are considered (territorial distribution of sites; instability of the external environment; high labor intensity of logistics operations; significant restrictions on storage and access to materials; need for integration with calendar and network schedules of work). An algorithm for developing and implementing a communication strategy for managing material flows in construction is proposed, covering key stages from planning to control, adjustment and use of modern digital technologies. The stages of implementing a communication strategy in the process of managing material flows at construction enterprises are highlighted. It is substantiated that compliance with this algorithm provides integrated management of information and material flows, which significantly increases the efficiency of construction projects. A package of measures is proposed to assess the impact of rational communications on logistics risks and consumer purchasing behavior: identification and classification of logistics risks; analysis of the existing communication strategy; determination of target segments of consumers and their information needs; collection of data on purchasing behavior and reaction to communications; modeling and assessment of the impact; development of recommendations and adjustment of the communication strategy. It is substantiated that the approach to managing material flows at construction enterprises should be based on digitalization, standardization and integration of logistics with effective communications. The proposed recommendations are aimed at optimizing business processes, reducing costs, increasing competitiveness, and ensuring sustainable development of construction enterprises.
Keywords: marketing communications; logistics; strategies; consumers; construction; material flow